AI-Enhanced Screening: Analisis Swing Trade Pada Saham Indeks KOMPAS100 Menggunakan Perplexity Finance - Budi Wasito; Sigit Birowo; Brastoro Brastoro (Jurnal Abdimas: Sosial, Bisnis, dan Lingkungan, 2026)
The development of artificial intelligence (AI) technology over the past decade has transformed various sectors, including the financial world and capital markets. AI is now capable of processing massive amounts of data at high speed, providing more accurate analysis and identifying patterns that are difficult for human observers to detect. This transformation has given rise to a new approach to investment analysis—where speed, accuracy, and computational intelligence play a crucial role in decision-making. In the context of stock analysis, AI offers far more efficient screening and evaluation methods. In fundamental analysis, AI can process financial reports, key ratios, news sentiment, and even industry trends in real time. Meanwhile, in technical analysis, AI can read price patterns, detect momentum, analyze volatility, and present objective trading signals. The combination of the two creates a more comprehensive, data-driven trading approach with minimal subjective bias. This use of AI is particularly relevant in Indonesia, where indices like the KOMPAS100 reflect a collection of leading stocks that have the potential to provide attractive investment and trading opportunities. However, many traders and investors still conduct analysis manually, often falling prey to bias, misreading momentum, or failing to understand the inherent risks. Therefore, literacy is needed on how AI—through platforms like Perplexity Finance—can be used to improve the quality of both fundamental and technical analysis with greater systematicity and accuracy.